log(1-x)/x[1/2,0]などの定積分

\begin{alignat}{2}
&(1) \displaystyle\int_0^{\frac{1}{2}} \frac{\log (1-x)}{x}dx=\frac{1}{2}(\log 2)^2-\frac{π^2}{12}\\
&(2) \displaystyle\int_0^1 \frac{1}{x}\log \left(1-\frac{x}{2}\right)dx=\frac{1}{2}(\log 2)^2-\frac{π^2}{12}\\
&(3) \displaystyle\int_0^1 \frac{1}{1-x} \log \frac{1+x}{2}dx=\frac{1}{2}(\log 2)^2-\frac{π^2}{12}\\
\end{alignat}










<証明>

\begin{alignat}{2}
&(1) \displaystyle\int_0^{\frac{1}{2}} \frac{\log (1-x)}{x}dx=-\displaystyle\int_0^{\frac{1}{2}} \frac{1}{x}\left(\displaystyle\sum_{n=0}^{\infty} \frac{x^{n+1}}{n+1}\right)dx=-\displaystyle\sum_{n=0}^{\infty}\frac{1}{n+1}\displaystyle\int_0^{\frac{1}{2}}x^ndx\\
&                   =-\displaystyle\sum_{n=0}^{\infty}\frac{1}{n+1}\left[\frac{x^{n+1}}{n+1}\right]_0^{
\frac{1}{2}}=-\displaystyle\sum_{n=0}^{\infty} \frac{1}{2^{n+1}(n+1)^2}\\
&                   =-\displaystyle\sum_{n=0}^{\infty} \frac{1}{2^n \cdot n^2}=-\mathrm{Li}_2\left(\frac{1}{2}\right)=\frac{1}{2}(\log 2)^2-\frac{π^2}{12}
\end{alignat}以上より$$\displaystyle\int_0^{\frac{1}{2}} \frac{\log (1-x)}{x}dx=\frac{1}{2}(\log 2)^2-\frac{π^2}{12}$$







\((2)\) \(x=2t\) と置きます。\((dx=2dt)\)$$\displaystyle\int_0^1 \frac{1}{x}\log \left(1-\frac{x}{2}\right)dx=\displaystyle\int_0^{\frac{1}{2}}\frac{\log (1-t)}{2t} \cdot 2dt=\displaystyle\int_0^{\frac{1}{2}} \frac{\log (1-t)}{t}dt=\frac{1}{2}(\log 2)^2-\frac{π^2}{12}$$以上より$$\displaystyle\int_0^1 \frac{1}{x}\log \left(1-\frac{x}{2}\right)dx=\frac{1}{2}(\log 2)^2-\frac{π^2}{12}$$







\((3)\) \(1-x=t\) と置きます。\((dx=-dt)\)$$\displaystyle\int_0^1 \frac{1}{1-x} \log \frac{1+x}{2}dx=\displaystyle\int_1^0 \frac{1}{t}\log \frac{2-t}{2}(-dt)=\displaystyle\int_0^1 \frac{1}{t}\log \left(1-\frac{t}{2}\right)dt=\frac{1}{2}(\log 2)^2-\frac{π^2}{12}$$以上より$$\displaystyle\int_0^1 \frac{1}{1-x} \log \frac{1+x}{2}dx=\frac{1}{2}(\log 2)^2-\frac{π^2}{12}$$

コメントを残す

メールアドレスが公開されることはありません。 * が付いている欄は必須項目です